2016
DOI: 10.1115/1.4033632
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Fault Energy Maps of Fe–Mn–Al–C–Si Steels: Effect of Temperature, Grain Size, and Variations in Compositions

Abstract: A subregular solution thermodynamic model was employed to calculate the stacking fault energy (SFE) in Fe–Mn–Al–C–Si steels with contents of carbon 0.2–1.6 wt.%, manganese 1–35 wt.%, aluminum 1–10 wt.%, and silicon 0.5–4 wt.%. Based on these calculations, temperature-dependent and composition-dependent diagrams were developed in the mentioned composition range. Also, the effect of the austenite grain size (from 1 to 300 μm) on SFEs was analyzed. Furthermore, some results of SFE obtained with this model were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 64 publications
2
52
0
3
Order By: Relevance
“…Recently it was concluded, using ab-initio calculations, that the carbon increase the SFE in Fe-C [170] and FCC for pure iron [141,171]. Additionally, the variation of the SFE with the carbon and aluminum content for the Fe-Mn-Al-C system [161] is shows in Figure 20. Figure 19.…”
Section: Chemical Composition Effectmentioning
confidence: 93%
See 4 more Smart Citations
“…Recently it was concluded, using ab-initio calculations, that the carbon increase the SFE in Fe-C [170] and FCC for pure iron [141,171]. Additionally, the variation of the SFE with the carbon and aluminum content for the Fe-Mn-Al-C system [161] is shows in Figure 20. Figure 19.…”
Section: Chemical Composition Effectmentioning
confidence: 93%
“…the TRIP and TWIP effects are reduced or suppressed in fine grain sizes [133,174,175] or promoted in coarse grain sizes [172]. The variation of the SFE with the austenitic grain size in the Fe-Mn-Al-C system [161] is shows in Figure 21. Recently, it was reported that Nb additions in Fe-Mn-Al-C steels [176], produced a drastic decrease of the twin activity, mainly caused by the grain size refinement in the microstructure.…”
Section: Chemical Composition Effectmentioning
confidence: 95%
See 3 more Smart Citations